If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 6)(x + -1) = 0 Reorder the terms: (6 + x)(x + -1) = 0 Reorder the terms: (6 + x)(-1 + x) = 0 Multiply (6 + x) * (-1 + x) (6(-1 + x) + x(-1 + x)) = 0 ((-1 * 6 + x * 6) + x(-1 + x)) = 0 ((-6 + 6x) + x(-1 + x)) = 0 (-6 + 6x + (-1 * x + x * x)) = 0 (-6 + 6x + (-1x + x2)) = 0 Combine like terms: 6x + -1x = 5x (-6 + 5x + x2) = 0 Solving -6 + 5x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-6 + -1x)(1 + -1x) = 0Subproblem 1
Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-6, 1}
| x^2+11x+9=0 | | 19r+2s+11r+7s= | | 2n=6n-220 | | (2x-1)(x+2)=0 | | 4k+4=16 | | (t*9)+(t*8)= | | 34-79b-78-6d+4+6d= | | -20-(-50)=0.11 | | 2x+10=x+71 | | (5+2x)3=7+(4)x | | (2x-1)(5d+5)=0 | | 440000+2x=1320000+3x | | 36-70d-72-8d+8+6d= | | 2b-5-12b-4= | | 5x-16=-13x-27 | | 12x-5y=60 | | 6x-(5x+6)=3x-26 | | 2y=3x+5 | | (x-30)(x-120)=0 | | 8q-12=3q-23 | | 2t-1=3t+21 | | 440000-1320000+2x-2x=132000-132000+3x-2x | | 4x-5=10x+13 | | 7x-8=6x-5 | | 2(y+3)=3(y-3) | | (7+2x)4=10+(5)x | | -4(2x-6)=10-(x-4) | | (a+4)(a-5)=0 | | 4x-4=3x+5 | | 12x=11x-21 | | (13)(b+5)=0 | | x^2-1x-12=0 |